Do the Biggest Aisles Serve a Brighter Future? Global Retail Chains and Their Implications for Romania - Javorcik, Beata S. (World Bank, Washington, DC, 2012)
During the past two decades many economies have opened their retail sector to foreign direct investment, yet little is known about possible implications of such liberalization on the economies of developing host countries. Using firm-level data from Romania, this study examines how the presence of global retail chains affects firms in the supplying industries. Applying a difference-in-differences method, the econometric analyses yield the following conclusions. The expansion of global retail chains leads to a significant increase in the total factor productivity in the supplying industries. Their presence in a region increases the total factor productivity of firms in the supplying industries by 15.2 percent and doubling the number of chains leads to a 10.8 percent increase in total factor productivity. However, the expansion benefits larger firms the most and has a much smaller impact on small enterprises. This conclusion is robust to several extensions and specifications, including the instrumental variable approach. These results suggest that the opening of the retail sector to foreign direct investment may stimulate productivity growth in upstream manufacturing and extend our understanding of foreign direct investment in service sectors.